Theory and Practice of Metal Electrodeposition - Gamburg, Yuliy D.; Zangari, Giovanni; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This book provide new insights into the theoretical and applied aspects of metal electrodeposition. The theory largely focuses on the electrochemistry of metals. Details on the practice discuss the selection and use of metal coatings, the technology of deposition of metals and alloys, including individual peculiarities, properties and structure of coatings, control and investigations. This book aims to acquaint advanced students and researchers with recent advances in electrodeposition, while also being an excellent reference for the practical electrodeposition of metals and alloys.
Basic terms and concepts -- The structure of the metal-solution interface -- Electrochemical thermodynamics and electrochemical kinetics -- Influence of diffusion on the rate of electrochemical process -- Nucleation -- Morphology of the growing metal surface -- Potential distribution in the volume of solution and current distribution on the electrode surface -- Current density distribution on rough surfaces -- Using of pulse and periodic currents in electrodeposition and in electrochemical experiments -- Electrodeposition of alloys -- Codeposition of impurities. Hydrogenation -- Technologies for deposition of several metals and alloys -- Structure of electrodeposited metals and alloys -- Physical properties of deposited macrolayers of metals and alloys. Control of quality and testing methods -- Conclusion.
Keywords: Chemistry; Materials; Nanotechnology; Chemistry, inorganic; Chemistry; Electrochemistry; Tribology, Corrosion and Coatings; Nanotechnology; Materials Science, general